Unraveling the effects of tropical cyclones on economic sectors worldwide - Sven Kunze (University of Heidelberg, Department of Economics, 2017)
This paper unravels the contemporaneous, lagged, and indirect effects of tropical cyclones on annual sectoral growth worldwide. The main explanatory variable is an area-weighted measure for local tropical cyclone intensity based on meteorological data, which is included in a panel analysis for a maximum of 213 countries over the 1971-2015 period. I find that the significantly negative influence of tropical cyclones on aggregate GDP growth can be attributed to contemporaneous negative effects on three sector aggregates including agriculture, infrastructure, as well as trade and tourism. In subsequent years, tropical cyclones negatively affect nearly all sectors. However, the Input-Output analysis shows that production processes are sticky and indirect economic costs of tropical cyclones are low.
urn:nbn:de:bsz:16-heidok-237578
Keywords: E23; O11; O17; O44; Q51; Q54; Q56; 330; Tropical Cyclones; Sectoral Economic Growth; Environment and Growth; Natural Disasters; Input-Output Analysis